2020
DOI: 10.1097/mao.0000000000002571
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Furosemide Enhances the Magnetic Resonance Signal of Systemic Gadolinium in the Mammalian Cochlea

Abstract: Hypothesis: Furosemide alters the permeability of the intrastrial fluid–blood barrier. Background: The cochlear sensory cells are protected by the blood-perilymph and intrastrial fluid–blood barriers, which hinder substances, including gadolinium-based contrast agents (GdCAs), to enter the endolymphatic space. High-dose furosemide causes transient shift of hearing thresholds and morphological changes in stria vascularis. Furosemide is also known to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The areas correspond to capillary networks in the inner ear, suggesting entry of GBCA at the blood-labyrinth barrier. Comparison of different GBCA found some variation in signal intensity and uptake kinetics, but intravenous administration of both macrocyclic and linear agents reliably led to enhancement of perilymph ( 20 , 21 ). In mice, all GBCAs led to enhancement of perilymph with increasing intensity over time from 15–105 min ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The areas correspond to capillary networks in the inner ear, suggesting entry of GBCA at the blood-labyrinth barrier. Comparison of different GBCA found some variation in signal intensity and uptake kinetics, but intravenous administration of both macrocyclic and linear agents reliably led to enhancement of perilymph ( 20 , 21 ). In mice, all GBCAs led to enhancement of perilymph with increasing intensity over time from 15–105 min ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in addition to reducing the EP, furosemide may reduce auditory sensitivity through other mechanisms. Loop diuretics weaken the blood labyrinth barrier by damaging the tight junctions lining the stria vascularis, an effect that has been exploited to enhance the uptake of contrast agents in magnetic resonance imaging studies (58). The ototoxicity of other agents such as cisplatin or aminoglycosides increases when administered simultaneously with loop diruetics such as furosemide, likely because of the increased permeability of the drugs in the perilymphatic spaces of the cochlea (59).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the permeability of the blood-perilymph barrier in the chinchilla demonstrate that EP loss after furosemide administration is correlated to the concentration of the drug in perilymph (Juhn and Rybak, 1981 ). More recent findings in an MRI study showed a much slower opening of the intrastrial fluid-barrier after the administration of a high dose of furosemide (Videhult Pierre et al, 2020 ) than the expected loss of EP. We, therefore, consider the observation of a more rapid loss of NKCC1 in type II fibrocytes than in marginal cells, to be consistent with previous experiments on inner ear barriers and the differences in the permeability of the barriers might be a mechanism behind the more rapid effect on the type II fibrocytes of furosemide.…”
Section: Discussionmentioning
confidence: 95%
“…Stimulation of PEDF production was reported to increase the survival of PVM/M in cell culture and stimulate the formation of tight junctions (Zhang et al, 2021 ). It could therefore be part of a counter mechanism to the increased permeability of the intrastrial fluid-blood barrier caused by furosemide (Videhult Pierre et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%